Analisis Implementasi Pembelajaran Berbasis Neurosciencie - Yeni Alfina; Masduki Asbari; Siti Habibah (Journal of Information Systems and Management (JISMA), 2024)
This research aims to find out the concept of Mr. Munif Chatib's thoughts about learning and education. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to oral narratives from the Risal Tv YouTube channel delivered by Mr. Munif Chatib entitled "Brain-Based Learning". The results of this study explain how teachers convey concepts. learning to students by working the brain and not easily forgetting. This theory was applied by Munif Chatib to education in Indonesia, namely the strategy in teaching is student center, namely by choosing the best modality, the activity assumes that all students are intelligent and have different intelligences that cannot be equalized, therefore teachers must understand students so that they can apply learning that suits their respective intelligence